"Me I don't really discuss anything with them": Parent and teacher perceptions of early childhood education and parent-teacher relationships in Ghana. (2020) - Wolf, Sharon
Highlights: Parents prioritize academics and structural resources when determining ECE quality. Parents view their role primarily as ensuring children have basic necessities met. Parents and teachers have varied perspectives on how to discipline children. Teachers feel frustrated in their attempts to communicate with parents. Efforts to engage parents in ECE should consider parent-teacher relationships. Abstract: Parental involvement in early childhood education (ECE) is presumed to be important. Yet little research exists on how parents view their role in their child's early schooling, nor on how parent-teacher relationships may shape classrooms. This is particularly true in low- and middle-income countries. This study analyzes interviews with 25 parents and 25 teachers of children in pre-primary school in the Greater Accra Region of Ghana. Interviews investigated perceptions about educational quality, experiences with ECE, communication between parents and teachers, and roles of parents and teachers in children's education. Results revealed important areas of both alignment and misalignment between parents' and teachers' perceptions and goals for children's ECE experiences. Implications for ECE policy and parental engagement are discussed.